Activation of Yes-Associated Protein/PDZ-Binding Motif Pathway Contributes to Endothelial Dysfunction and Vascular Inflammation in AngiotensinII Hypertension - Xu, Qian; Zhuo, Kunping; Cai, Ruiping; Su, Xiaomin; Zhang, Lu; Liu, Yueyang; Zhu, Lin; Ren, Fu; Zhou, Ming-Sheng (Frontiers in Physiology, 2021)
Yes-associated protein (YAP) and its associated coactivator of PDZ-binding motif (TAZ) are co-transcriptional regulators and down effectors of Hippo signaling pathway. Recent studies have shown that the Hippo/YAP signaling pathway may play a role in mediating vascular homeostasis. The present study investigated the role of YAP/TAZ in endothelial dysfunction and vascular inflammation in angiotensin (Ang)II hypertensive mice. The infusion of AngII (1.1 mg/kg/day by mini-pump) for 3 weeks induced the activation of YAP/TAZ, manifested by decreased cytosolic phosphor-YAP and phosphor-TAZ and increased YAP/TAZ nuclear translocation, which were prevented by YAP/TAZ inhibitor verteporfin. AngII significantly increased systolic blood pressure (SBP), macrophage infiltration and expressions of proinflammatory cytokines, impaired endothelial function in the aorta of the mice. Treatment with verteporfin improved endothelial function and reduced vascular inflammation with a mild reduction in SBP. AngII also induced YAP/TAZ activation in Human umbilical vein endothelial cells in vitro, which were prevented by LB-100, an inhibitor of protein phosphatase 2A (PP2A, a major dephosphorylase). Treatment with LB-100 reversed AngII-induced proinflammatory cytokine expression and impairment of phosphor-eNOS expression in vitro. Our results suggest that AngII induces YAP/TAZ activation via PP2A-dependent dephosphorylation, which may contribute to the impairment of endothelial function and the induction of vascular inflammation in hypertension. YAP/TAZ may be a new target for hypertensive vascular injury.